PROTOCOLO DIGITAL PARA PROJETO CONCEITUAL E VALIDAÇÃO DE UMA ÓRTESE TORNOZELO-PÉ - Rui Araújo Júnior; Patrícia Maria de Moraes Barros Fucs (Acta Ortopédica Brasileira)
Abstract Objective: This original article aimed to develop a digital protocol for the conceptual design and validation of Ankle-Foot Orthoses (AFO) using 3D mapping technologies. Methods: A scanned model of the ankle-foot complex of a 12-year-old child with a drop foot was utilized, along with a generic AFO model from a Computer-Aided Design environment. Autodesk Meshmixer and Fusion software were employed for conceptual design and static load analysis. Results: The static load analysis using the Von Mises failure criterion on the AFO model with ABS material demonstrated structural integrity under critical loading conditions. The digital protocol facilitated the design of a functional and patient-specific AFO orthosis. Conclusions: The study successfully established a digital workflow for AFO design and validation, showcasing the potential of 3D technologies in creating customized orthoses for lower limb rehabilitation. Level of Evidence IV; Descriptive Study.